The origins of European integration : the pre-history of today's European Union, 1937-1951 - Segers, Mathieu, 1976-2023 1976-2023 (Cambridge University Press, 2024)
Bringing together political, diplomatic, economic, cultural, and contemporary history, this book explores why and how European integration came to pass. It tells a fascinating story of ideals and realpolitik, political dreams and geographical realities, and planning and chaos. Mathieu Segers reveals that the roots of today's European Union lie deep in Europe's past and encompass more than war and peace, or diplomacy and economics. Based on original archival and primary source research, Segers provides an integrated history of the beginnings of European integration and the emergence of post-war Western Europe and today's European Union. The Origins of European Integration offers a broad perspective on the genealogy of post-war Western Europe, providing readers with a deeper understanding of contemporary European history and the history of transatlantic relations